Forest Tree Introduction in India, its Scope and Importance - Sahni, K. C. (Indian Forester, 1965)
The imporlance of tree introduction and the benefits arising from some of the outstanding introductions are emphasized. Methodology employed in plant introduction, viz., collection of climatic data, information regarding provenance, range of distribution, introductions from centres of origin, preliminary testing, quarantine measures, etc., are discussed. An inventory of successful introductions has been outlined.